Implementation of local agenda 21's education, awareness and training component: a case study of Gaborone - Mogotsi, Barulaganye Jones (Rhodes University, Faculty of Education, Department of Education, 2006)
What is required is the 'politics of the rhizome' in which everyone, every community, every nation and every major region comes to terms with the uniqueness of their situation and acts accordingly "“ and realises that it is only by vast numbers of people, of groups and organizations acting in accordance with possibilities of their situations, that the environmental crisis will be solved.' (Gare, 1995:161). The study investigates the implementation of Local Agenda 21's education, awareness and training component by the Gaborone City Council Environmental Health Department (GCCEHD) to address environmental challenges facing the city of Gaborone, the capital city of Botswana. The research was conducted as a qualitative case study that made use of semi-structured interviews, focus group interviews and document analysis as instruments of data generation. Samples of respondents were selected from the Gaborone City Council (GCCEHD) employees in management positions, workers, and elected political councillors. The study is contextualised through establishing environmental issues in the Gaborone City Council, identifying strategies to address environmental issues and the review of the Waste Management Plan 2003-2009, which the department uses as a guiding document for waste management. The study establishes that the council employees are mostly concerned with issues of waste management and need commitment from all Local Government sectors of the work force. The study established the importance of education, awareness and training as a response to environmental issues facing Gaborone. The study also establishes the need for social education in terms of public education, awareness and training needed for the public to adequately respond to environmental challenges in their context. Models and relevant policy and guiding documents such as the Vision for Greater Gaborone, DPSEEA Model and Botswana Environmental Planning Principles were identified and recommended for the department to consider. The awareness and training activities should be developed and involve the community in environmental management. This should enable the council to create opportunities for income generation, at the same time changing community negative attitudes towards the environment and improving service delivery by the department.
Keywords: Environmental education -- Botswana -- Gabarone -- Case studies; Environmental education -- Activity programs; Environmental health -- Botswana -- Gabarone -- Case studies; Sustainable development -- Botswana; Environmental policy -- International cooperation; Environmental protection -- Botswana